2023
DOI: 10.1093/ofid/ofad102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hypoalbuminemia on Ceftriaxone Treatment Failure in Patients With Enterobacterales Bacteremia: A Propensity-Matched, Retrospective Cohort Study

Abstract: Objectives Ceftriaxone is frequently prescribed due to its convenience of dosing and robust antimicrobial activity. However, patients with hypoalbuminemia may experience suboptimal ceftriaxone exposure due to the high degree of protein binding. We aim to evaluate the impact of hypoalbuminemia on treatment failure among hospitalized adults with Enterobacterales bacteremia who received ceftriaxone therapy. Methods We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…11 In a recent observational cohort study, hypoalbuminemia did not appear to affect clinical outcomes for patients with Enterobacterales bacteremia treated with ceftriaxone, but the authors noted that numerically more incidences of treatment failure were observed among critically ill patients with hypoalbuminemia. 12 These studies beg the question if there is a need to consider alternative dosing strategies for ertapenem given the similarities to ceftriaxone. Patients within our cohort were matched in part on lowest albumin at admission, and most patients included were hypoalbuminemic both at admission and at carbapenem initiation.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a recent observational cohort study, hypoalbuminemia did not appear to affect clinical outcomes for patients with Enterobacterales bacteremia treated with ceftriaxone, but the authors noted that numerically more incidences of treatment failure were observed among critically ill patients with hypoalbuminemia. 12 These studies beg the question if there is a need to consider alternative dosing strategies for ertapenem given the similarities to ceftriaxone. Patients within our cohort were matched in part on lowest albumin at admission, and most patients included were hypoalbuminemic both at admission and at carbapenem initiation.…”
Section: Discussionmentioning
confidence: 99%